To'dok Telok, Manre Ka'dok: Islamic Traditions, Bugis Cultural Identity, and Maritime Communities on Kemujan Island, Karimunjawa - Widodo Wikandono; Faiq Firni Ramadhan; Siti Rohmah; Hafidz Fadli (Sutasoma : Jurnal Sastra Jawa, 2026)
This article discusses the transformation of the Ma Maulu’ tradition—a Maulid celebration of Prophet Muhammad with Bugis characteristics—into the To’dok Telok Manre Ka’dok festival on Kemujan Island, Karimunjawa, Central Java. The article aims to explain how this tradition functions as a medium for cultural preservation, collective identity formation, and the representation of maritime culture among the multi-ethnic community on Kemujan Island. Using a qualitative ethnographic approach through participant observation, in-depth interviews, and document analysis, this research is analyzed from the perspectives of Clifford Geertz's (1973) interpretive anthropology and Koentjaraningrat's (2009) acculturation theory. The results show that this festival is not only a religious celebration but also a space for the negotiation and reproduction of Bugis values, local Islamic spirituality, and maritime identity. The To’dok Telok (egg skewer) and Manre Ka’dok (eating together) symbols represent the balance between this world and the afterlife, social solidarity, and cross-ethnic cohesion amid the growing tourism in Karimunjawa. Based on these findings, we argue that To’dok Tello’ Manre Ka’dok has developed into a symbol of collective cultural transformation that goes beyond Bugis ethnic identity and has become a shared cultural heritage for the people of Kemujan Island, Karimunjawa.